Ethical leadership in and through the family, religious, secular traditions and the youth - Dames, GE (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
This article describes the ethical roles of the Family, Religious and Secular Traditions, and Youth as an attempt to explore and reflect on new ways of moral formation and transformation. Challenges of the 21st century seem to overpower any interventions for a morally good society. The ‘societal homes’ in which ordinary 21st century families and youths lives in, have become unsafe and unpredictable. Religious and secular institutions’ roles are neither certain nor trustworthy. Moral and ethical challenges of our day play itself out in a ‘vacuum’ of a ‘free for all’ tendency. The socio-economic reality of South Africa exacerbates the problem of responsible and morally good citizenry. Dysfunctional families are the direct cause for the moral decay; and calls for ‘a living hope’ that inspires families and youth to become active agents with new ethical and moral values. Families are the most powerful agent of socialisation. Spiritual leaders could assist in the creation of a new ‘sense of the world’. South Africans have a common ethical calling and responsibility, and should build a national culture of integrity. Families, youths and religious societies are the most basic agents for moral and ethical formation and transformation.